Machine translated letters of credit of real-life trade exchange from English to Chinese: a qualitative approach to the evaluation of machine translation - Zhu, Xiaowei (Nanyang Technological University, 2022)
International trade documents are very important in trade transactions. Letters of credit in international trade are one of the most widely used transaction methods. Many letters of credit require translation from one language to another, which has contributed to a high demand for machine translation (MT) by many companies mainly due to the low cost and fast speed in comparison with human translation.